TOTAL BACTERIA AND IDENTIFICATION OF PROTEOLYTIC RUMINAL AND RETICULUM BACTERIA FROM LOCAL KACANG GOAT - Safika Safika; Darmawi Darmawi; Fitria Sari Ramadhani; Nurhaspika Nurhaspika; Moliwati Moliwati (Universitas Syiah Kuala, 2018)
This study aimed to calculate the total bacteria and to identify the proteolytic bacteria in rumen and reticulum of local Kacang goat. The samples used were the rumen and reticulum fluids of five goats at abattoirs in Banda Aceh. Isolation of proteolytic bacteria was carried out using skim milk agar with pour plate method and incubated at 39° C for 48 hours. The bacterial colonies morphology was observed and the total bacterial count was recorded. DNA of the widest proteolytic index colony was isolated, amplified, and sequenced. The results showed that the dominant colonies morphology was white with position inside the agar. The average of total proteolytic bacteria in goat rumen fluid and reticulum fluid were 6.416x106 CFU/mL and 2,382x107 CFU/mL, respectively. Isolates with the widest proteolytic index was Ru3 (2.5 mm) in the rumen which homology and phylogenetic tree analysis of 16S rRNA showed 93% sequence similarity with Bacillus subtilis, while in reticulum was Re1 (2.0 mm) which has 92% sequence similarity to Tatumella. It is concluded that the number of proteolytic bacteria in reticulum is greater than the number of proteolytic bacteria in the rumen of local kacang goat. Homology analysis in this study proved that the Ru3 and Re1 isolate were probably either a new species or unconfirmed species.